2001
DOI: 10.1590/s1516-44462001000600009
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos neuropsicológicos do transtorno obsessivo-compulsivo

Abstract: Neuropsychology is contributing to elucidate the nature of brain dysfunction associated with obsessive-compulsive disorder (OCD). Neuropsychological studies of individuals with subclinical and clinical obsessive-compulsive symptoms are reviewed here. It was observed that OCD patients may display impaired "reality monitoring", memory for actions, non-verbal memory, visuo-spatial abilities, and executive functions. Some specific neuropsychological findings are associated with different clinical characteristics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1 It has been proposed that OCD affects the basal ganglia and frontostriatal structures, with consequent impairment of executive functions. 2,3 The term "executive functions" is quite broad and encompasses various psychological functions. Executive functions that have been associated with OCD include mental flexibility, nonverbal memory, verbal memory, visuospatial skills, psychomotor speed, and strategic planning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 It has been proposed that OCD affects the basal ganglia and frontostriatal structures, with consequent impairment of executive functions. 2,3 The term "executive functions" is quite broad and encompasses various psychological functions. Executive functions that have been associated with OCD include mental flexibility, nonverbal memory, verbal memory, visuospatial skills, psychomotor speed, and strategic planning.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It has been demonstrated that strategic planning, defined as "the ability to organize information into its most simple (or semantically related) components, making it easier to learn and memorize", is impaired in patients with OCD. 2,3 Dysfunction in strategic planning can lead to an excessive concern with details, lack of semantic associations, difficulty in modifying the cognitive stage, and impairment in nonverbal memory. 2 Mataix-Cols et al reported that OCD patients used unproductive organizational strategies during the copy portion of the Rey-Osterrieth Complex Figure Test (ROCFT), thereby corroborating the findings of Oliveira.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that obsessive/compulsive individuals present low competence in planning activities and organizational strategies (14,15), which reflects on EF deficits. Therefore, once BED is related to binge eating episodes, and as it is the main criteria for diagnosis, it plays a significant role in the development and maintenance of obesity and eating disorders.…”
Section: Introductionmentioning
confidence: 99%